1993
DOI: 10.1111/j.1476-5381.1993.tb13810.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrophysiological studies on the positive inotropic effect of 2‐phenyl‐4‐oxo‐hydroquinoline in rat cardiac tissues

Abstract: 1 The pharmacological and electrophysiological effect of 2-phenyl-4-oxo-hydroquinoline (YT-1), a new synthetic agent, were determined in rat isolated cardiac tissues and ventricular myocytes. 2 YT-1 was found to have a positive inotropic effect in both atria and ventricular muscles but did not cause significant increases in the spontaneously beating rate of right atria.3 The positive inotropic effect of YT-1 was antagonized neither by P-nor by a-adrenoceptor antagonists but was partially antagonized by a Ca2" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The class III antiarrhythmic agents exert their antiarrhythmic effects by suppressing the K outward currents to prolong the action potential duration and thereby increase the refractoriness of the conduction system (Singh & Nademanee, 1985;Hondeghem & Katzung, 1987;Imaizumi & Giles, 1987;Dukes et al, 1990;Kurachi et al, 1990;Su et al, 1990;1993;Gwilt et al, 1991). Our results showed that N-allylsecovoldine could suppress the IKI and the Ito, which consequently prolonged the action potential duration and increased further the refractoriness of the myocardium.…”
Section: Modification Of the Electrophysiological Properties Of The Cmentioning
confidence: 99%
“…The class III antiarrhythmic agents exert their antiarrhythmic effects by suppressing the K outward currents to prolong the action potential duration and thereby increase the refractoriness of the conduction system (Singh & Nademanee, 1985;Hondeghem & Katzung, 1987;Imaizumi & Giles, 1987;Dukes et al, 1990;Kurachi et al, 1990;Su et al, 1990;1993;Gwilt et al, 1991). Our results showed that N-allylsecovoldine could suppress the IKI and the Ito, which consequently prolonged the action potential duration and increased further the refractoriness of the myocardium.…”
Section: Modification Of the Electrophysiological Properties Of The Cmentioning
confidence: 99%
“…Among them, many alkaloids were found to have vasorelaxing [12,38,39] or antiarrhythmic activities [23, 40-42, 44, 48]. Consistent with their antiarrhythmic activities, electrophysiological studies revealed that these agents block cardiac Na + channels [35,36,45] and prolong the duration of action potential by inhibition of potassium outward currents [18,33,35,36,43].…”
Section: Introductionmentioning
confidence: 93%
“…The leftward-shift of the potential-dependent steadystate inactivation curve of Ito by JKL1073A is similar to previous observations with dicentrine (Su et al, 1994b), but differs from clofilium (Castle, 1990b), propafenone (Duan et al, 1993), bupivacaine (Castle, 1990a), 2-phenyl-4-oxo-hydro- Figure 8a from the total current. quinoline (Su et al, 1993) and quinidine (Clark et al, 1995). A biphasic inhibition of It.…”
Section: Mechanism Of the Blocking Action Of Jkl1073a And Comparison mentioning
confidence: 99%
“…Rat single cells were isolated by procedures previously described (Mitra & Morad, 1985;Su et al, 1993). Briefly, the hearts were excised from rats and retrogradely perfused in a Langendorff apparatus with Ca2+-free HEPES-buffered Tyrode solution.…”
Section: Isolation Of Rat Atrial Myocytesmentioning
confidence: 99%